Effectiveness of School Operational Aid Fund Management (BOS) in Improving the Quality of Education (Vocational School Case Study Negeri 2 Kediri City) - Weny, Siska Yulia (Proceeding International Conference on Education, 2023)
This research aims to determine the effectiveness of managing School Operational Assistance (BOS) funds in improving the quality of education starting from planning, implementation, monitoring and evaluation, as well as the impact of BOS funds in improving the quality of education at SMK Negeri 2 Kediri City. The approach in this research uses qualitative. Meanwhile, the type of research used in this research is descriptive case study research. The techniques used to collect data are interview, observation and documentation methods. As a result of the research conducted, the author can conclude that the effectiveness of managing BOS funds in improving the quality of education at SMK Negeri 2 Kediri City can be said to be effective. This can be seen from the first point, planning for managing BOS funds at SMK Negeri 2 Kediri City begins with preparing RKAS based on needs and according to the financing components of BOS funds, especially to improve the quality of education. Second, the implementation of BOS fund management at SMK Negeri 2 Kediri City is adjusted to the RKAS which has been determined specifically to improve the quality of education. Third, supervision and evaluation of the management of BOS funds at SMK Negeri 2 Koa Kediri is carried out by the school principal and directly from the Kediri Education Service Branch. Evaluations are carried out at the end of every year to correct errors in the management of BOS funds. Fourth, the impact felt by SMK Negeri 2 Kota Kediri with the existence of BOS funds is that it can help with school operational costs, help finance teacher competency development and ease the burden on parents of students in education costs.